Differences in cerebral structure among patients with amnestic mild cognitive impairment and patients with Alzheimer’s disease - Cui, Xiaorui; Li, Mingpeng; Lei, Guanxiong; Wang, Jie; Pan, Jialin; Zhu, Sheng; Wu, Tao; Zou, Liangyu; Yan, Jianhui (Frontiers in Aging Neuroscience, 2024)
BackgroundBrain has been shown to undergo progressive atrophy in patients with Alzheimer’s disease (AD); however, more evidence is needed to elucidate how the brain structure changes during the progression to AD. Here, we observed differences in the cerebral structure among patients with amnestic mild cognitive impairment (aMCI) and patients with AD.MethodsA total of 46 participants were selected and divided into AD, aMCI, and healthy control (HC) groups. Structural magnetic resonance imaging (sMRI) was performed on all participants. Voxel-based morphometry (VBM) and surface-based morphometry (SBM) techniques were utilized to analyze sMRI data so as to identify significant differences among the specific brain regions of these three groups. Then, a correlation analysis was performed on the characteristics of the identified brain regions and the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) cognitive assessment scores.ResultsThe volume of the left precuneus region, which was identified by voxel-based morphometry, and the thickness of both sides of the inferior parietal, which was identified by surface-based morphometry, were shown to be less in AD/aMCI patients, compared to those of the HC. The correlation analysis showed that there were significant differences between the volume of the left precuneus region and the MMSE/MoCA scores, as well as between the thickness of the left and right sides of the inferior parietal region and the MMSE/MoCA scores.ConclusionThe sMRI characteristics of the identified brain regions were considered to be potential predictive diagnostic biomarkers for AD.Systematic review registrationIdentifier: ChiCTR2400092593.